A discussion of microplastics in soil and risks for ecosystems and food chains. (February 2023) - Li, Zhaolin; Yang, Yafeng; Chen, Xiangmeng; He, Yifeng; Bolan, Nanthi; Rinklebe, Jörg; Lam, Su Shiung; Peng, Wanxi; Sonne, Christian
Abstract: Microplastics are among the major contaminations in terrestrial and marine environments worldwide. These persistent organic contaminants composed of tiny particles are of concern due to their potential hazards to ecosystem and human health. Microplastics accumulates in the ocean and in terrestrial ecosystems, exerting effects on living organisms including microbiomes, fish and plants. While the accumulation and fate of microplastics in marine ecosystems is thoroughly studied, the distribution and biological effects in terrestrial soil call for more research. Here, we review the sources of microplastics and its effects on soil physical and chemical properties, including water holding capacity, bulk density, pH value as well as the potential effects to microorganisms and animals. In addition, we discuss the effects of microplastics in combination with other toxic environmental contaminants including heavy metals and antibiotics on plant growth and physiology, as well as human health and possible degradation and remediation methods. This reflect is an urgent need for monitoring projects that assess the toxicity of microplastics in soil and plants in various soil environments. The prospect of these future research activities should prioritize microplastics in agro-ecosystems, focusing on microbial degradation for remediation purposes of microplastics in the environment. Graphical abstract: Image 1 Highlights: Microplastics (MP) are emerging persistent organic pollutants with toxic properties. MPs pose significant environmental risks to living organisms and infiltrate human food chains. MPs accumulate in soils and affect the microbiome and plants. MPs infiltrate interact with other pollutants including heavy metals and antibiotics. Microbial degradation is a key pathway for remediation of microplastics.